DIGITAL MARKETING STRATEGY DESIGN IN INCREASING SALES VOLUME AT MSME CHIPS ALJANNAH - Miftahul Zannah; Husni Mubarak (SEAN Institute, 2023)
Micro, Small and Medium Enterprises (MSMEs) is one of the activities that increase growth, movement, and economic development. Economic development in Indonesia is one important part with the aim of improving the welfare of society. This study aims to how the design of Digital marketing strategies in increasing sales Volume at MSMEs chips Aljannah. Marketing strategy undertaken by SMEs chips Aljannah marketing mix marketing mix strategy is 7P. The method of data analysis in the study is qualitative research with descriptive methods by conducting interviews and observations as primary data and documentation as secondary data. The results of this study show that MSMEs chips Aljannah still apply traditional marketing without any specific marketing strategy and has not involved the role of digital marketing in making sales, digital marketing strategy design that has been prepared is expected to increase sales volume, brand image and expand the reach of consumers MSMEs chips Aljannah. The use of social media is very helpful for Aljannah chips MSMEs in marketing.